PENGARUH METODE PELATIHAN, INSTRUKTUR PELATIHAN, MATERI PELATIHAN DAN KOMPETENSI KERJA TERHADAP PRESTASI KERJA RELAWAN PAJAK (Studi Empiris pada Relawan Pajak 2019 Kantor Wilayah Direktorat Jenderal Pajak Jakarta Selatan II) - Ayu Aprilia; Puspita Rani (Universitas Budi Luhur, 2020)
This study aims to examine and analyze the effect of training methods, training instructors, training materials, and work competencies on tax volunteer work performance. This study uses a quantitative approach with a population of 92 tax volunteers 2019 Regional Office of South Jakarta DJP II. The type of data used is primary data obtained through questionnaires and distributed to samples determined through saturated sampling techniques, where all members of the population become research samples, but only 70 tax volunteers are obtained to complete the questionnaire. Data analysis techniques used multiple linear regression analysis. The results of this study indicate that partially the work competency variable has a significant positive effect on the achievement of tax volunteer work performance, but the training method, training instructor, and training material variables do not have a significant effect on tax volunteer work performance